Analytical study of charged boson stars with large scalar self-couplings - Nahomi Kan; Kiyoshi Shiraishi (European Physical Journal C: Particles and Fields, 2018)
Abstract We give good approximate analytic solutions for spherical charged boson stars in the large scalar-self-coupling limit in general relativity. We show that if the charge e and mass m of the scalar field nearly satisfy the critical relation $$e^2≈ Gm^2$$ e2≈Gm2 (where G is the Newton constant), our analytic expressions for stable solutions agree well with the numerical solutions.